Peningkatan Aktivitas dan Hasil Belajar Siswa pada Kompetensi Dasar Soal Cerita Perbandingan melalui Metode Scientific - Roch. Endah Herminingtyas (Universitas PGRI Semarang, 2019)
Indonesia's national juridical foundation in the opening of the 1945 Constitution states that Indonesia's national goal is to educate the nation's life, so the teacher as a pioneer of educational success has a big contribution to realize these goals. The problem in this study is how to increase student learning activities and outcomes on the basic competencies of comparative story through scientific methods. The method used in this writing is a qualitative descriptive method, the form is a class action. This research is a collaborative research (PTK). The subjects of this study were the sixth grade teachers and observers. The implementation of class action is carried out in 2 cycles. The results obtained were student learning activities in Cycle I obtained a score of 67.5%, and in Cycle II 87.5%. As for the learning outcomes obtained by students after participating in the learning of comparative story problems by applying scientific methods in Cycle I obtained an average score of 72.94% and in Cycle II obtained an average score of 82.35%.